Properties and intergranular phase analysis of a ZnO-CoO-Bi2O3varistor - W. Onreabroy (2018)
The electrical properties, microstructures and phase content of a ZnO-CoO-Bi2O3varistor have been characterised. High-resolution TEM and selected area electron diffraction provided detailed information on the distribution and structure of the intergranular Bi-rich phase. Triple points between the ZnO matrix grains contained crystallites that could be indexed to tetragonal β-Bi2O3, cubic γ-Bi2O3and δ-Bi2O3, or corresponding isostructural ZnO-Bi2O3phases. Thin-film, 1-2 nm grain boundaries were found to be amorphous, but for the first time, crystalline precipitates (with the β-Bi2O3type structure) were also detected in some thicker, 4-5 nm films. © 2005 Elsevier B.V. All rights reserved.